The Microplastics and Human Health: Focus on the Reproductive System - Trela, Katarzyna; Tuteja, Aleksander; Więcko, Laura; Olczyk, Liwia; Burzykowska, Klaudia; Gęborys, Kamila; Mohaissen, Rema; Tyla, Mikołaj; Stabrawa, Patryk (Quality in Sport, 2025)
Introduction: Plastic pollution, especially in the form of microplastics (MPs), is a growing global health concern. Due to their small size and chemical properties, MPs can enter the human body via ingestion, inhalation, or dermal absorption. Beyond accumulating in organs such as the lungs, liver, and kidneys, MPs have also been found in reproductive tissues. Aim: The aim of this review is to evaluate current evidence on the effects of MPs on male and female reproductive systems. Materials and Methods: A literature review of 57 studies published between 2004 and 2025 was conducted. Of these, 41 were from 2020–2025 and 39 were original research. The selection included in vivo and in vitro experiments, as well as human observational studies addressing exposure, tissue accumulation, toxicity, and reproductive outcomes. Results: Microplastics have been detected in both male and female reproductive organs. In females, MPs were primarily found in the placenta, follicular fluid, and endometrial tissue, and were associated with hormonal imbalances, impaired folliculogenesis, reduced oocyte quality, and endometrial dysfunction. In males, MPs mainly affect sperm quality, leading to sperm DNA damage. Decreased testosterone levels and testicular abnormalities were also observed. In vivo studies have shown that the mechanism of MP-induced reproductive toxicity involves oxidative stress, inflammation, and hormonal disruption. Conclusions: Microplastics may pose a serious threat to reproductive health, as confirmed by numerous in vivo studies. Alarmingly, the amount of evidence in humans is also increasing. Therefore, further research is needed to assess the long-term effects and to develop effective preventive strategies.